Upper End Vertebra of Proximal Thoracic Curve At T1 is a Novel Risk Factor of Postoperative Shoulder Imbalance in Lenke Type 2 Adolescent Idiopathic Scoliosis. Issue 5 (June 2023) - Isogai, Norihiro; Yagi, Mitsuru; Otomo, Nao; Maeda, Yoshihiro; Suzuki, Satoshi; Nori, Satoshi; Tsuji, Osahiko; Nagoshi, Narihito; Okada, Eijiro; Fujita, Nobuyuki; Nakamura, Masaya; Matsumoto, Morio; et al.
Study Design: Retrospective single-center study. Objective: We investigated the risk factors of postoperative shoulder imbalance (PSI) in patients with Lenke type 2 adolescent idiopathic scoliosis (AIS) including the position of preoperative upper end vertebra (UEV). Methods: Seventy-five patients with Lenke type 2 AIS who underwent posterior correction and fusion surgeries from 2008 to 2018 were included. We included only patients whose upper instrumented vertebrae were at T2. The patients were divided into 2 groups based on radiographic shoulder height (RSH) at final follow-up, namely PSI group and non-PSI group, and PSI was defined as RSH > 10 mm. UEV, RSH, Cobb angle, curve flexibility, T1 and T2 tilt, correction rate, Risser grade, Scoliosis Research Society-22 scores, and demographic data were compared between the groups using independent t- tests or chi-square tests. Variables with P value < 0.20 in univariate analysis were assessed in logistic regression analysis. Results: Thirty-four patients in the PSI group and 37 patients in the non-PSI group were analyzed. Univariate analysis revealed that there were more patients with UEV at T1 (PSI: 85%, non-PSI: 54%, P < 0.01) and Risser grade ≥ 3 (PSI: 88%, non-PSI: 62%; P < 0.05) in the PSI group than in the non-PSI group. Logistic regression analysis revealed that UEV at T1 (odds ratio [OR] = 4.1 [1.2–14.4], P < 0.05) and Risser grade ≥ 3 (OR = 3.9 [1.1–14.5], P < 0.05) are significantly associated with PSI. Conclusions: UEV at T1 and Risser grade ≥ 3 at the time of surgery are significant risk factors of PSI.